Improved cycling performance with ingestion of hydrolyzed marine protein depends on performance level - Vegge, G.; Ronnestad, B. R.; Ellefsen, S. (Journal of the International Society of Sports Nutrition, 2012)
The effect on performance of protein ingestion during or after exercise is not clear. This has largely been attributed to the utilization of different scientific protocols and the neglection of accounting for factors such as differences in physical and chemical properties of protein supplements and differences in athletic performance level. Methods We hypothesized that ingestion of unprocessed whey protein (15.3 g * h-1) together with carbohydrate (60 g * h-1), would provide no ergogenic effect on 5-min mean-power performance following 120 min cycling at 50% of maximal aerobic power (2.8 +/- 0.2 W * kg-1, corresponding to 60 +/- 4% of VO2max), compared to CHO alone (60 g * h-1). Conversely, we hypothesized that ingestion of the hydrolyzed marine protein supplement NutriPeptinTm (Np, 2.7 g * h-1), a processed protein supplement with potentially beneficial amino acid composition, together with a PROCHO beverage (12.4 g * h-1 and 60 g * h-1, respectively) would provide an ergogenic effect on mean-power performance. We also hypothesized that the magnitude of the ergogenic effect of NpPROCHO would be dependent on athletic performance. As for the latter analysis, performance level was defined according to a performance factor, calculated from individual pre values of Wmax, VO2max and 5-min mean-power performance, wherein the performance of each subject was ranked relative to the superior cyclist whos performance was set to one. Twelve trained male cyclists (VO2max = 65 +/- 4 ml * kg-1 * min-1) participated in a randomized double-blinded cross-over study. Results and conclusions Overall, no differences were found in 5-min mean-power performance between either of the beverages (CHO 5.4 +/- 0.5 W * kg-1; PROCHO 5.3 +/- 0.5 W * kg-1; NpPROCHO 5.4 +/- 0.3 W * kg-1) (P = 0.29). A negative correlation was found between NpPROCHO mean-power performance and athletic performance level (using CHO-performance as reference; Pearson R = 0.74, P = 0.006). Moreover, ingestion of NpPROCHO resulted in improved 5-min mean-power performance relative to ingestion of CHO in the six lesser performing subjects compared to the six superior performing subjects (P < 0.05). This suggests that with the current protocol, NpPROCHO provided an ergogenic effect on 5-min mean-power performance in athletes with a lower performance level.